Complementary roles of differential medial entorhinal cortex inputs to the hippocampus for the formation and integration of temporal and contextual memory (Systems Neuroscience). (2nd May 2020) - Marks, William D.; Yamamoto, Naoki; Kitamura, Takashi
Abstract: In humans and rodents, the entorhinal cortical (EC)‐hippocampal (HPC) circuit is crucial for the formation and recall of memory, preserving both spatial information and temporal information about the occurrence of past events. Both modeling and experimental studies have revealed circuits within this network that play crucial roles in encoding space and context. However, our understanding about the time‐related aspects of memory is just beginning to be understood. In this review, we first describe updates regarding recent anatomical discoveries for the EC‐HPC network, as several important neural circuits critical for memory formation have been discovered by newly developed neural tracing technologies. Second, we examine the complementary roles of multiple medial entorhinal cortical inputs, including newly discovered circuits, into the hippocampus for the temporal and spatial aspects of memory. Finally, we will discuss how temporal and contextual memory information is integrated in HPC cornu ammonis 1 cells. We provide new insights into the neural circuit mechanisms for anatomical and functional segregation and integration of the temporal and spatial aspects of memory encoding in the EC‐HPC networks. Abstract : Temporal information and contextual information are routed into the hippocampus by distinct inputs from the entorhinal cortex during memory formation. Both information streams converge in cornu ammonis 1 (CA1), where they are likely integrated. This review examines the underlying processes involved in this integrative activity and proposes new directions forward for examining the integration of time into existing engrams during memory formation.